2023
DOI: 10.3389/fimmu.2023.1089809
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of microRNA-222-3p ameliorates ulcerative colitis and colitis-associated colorectal cancer to protect against oxidative stress via targeting BRG1 to activate Nrf2/HO-1 signaling pathway

Abstract: Oxidative stress is an important pathogenic factor in ulcerative colitis (UC) and colitis-associated colorectal cancer (CAC), further impairing the entire colon. Intestinal epithelial cells (IECs) are crucial components of innate immunity and play an important role in maintaining intestinal barrier function. Recent studies have indicated that microRNA-222-3p (miR-222-3p) is increased in colon of UC and colorectal cancer (CRC) patients, and miR-222-3p is a crucial regulator of oxidative stress. However, whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
(77 reference statements)
0
12
0
Order By: Relevance
“…Targeting specific lncRNAs and miRNAs for silencing or overexpression provides therapeutic benefits, such as the inhibition of miR-222-3p for relieving DSS-induced damage of the colon. 139 Another approach is to utilize lncRNAs and miRNAs as potential therapeutic agents to target the relevant pathogenic factors. A noteworthy example of this is theaflavin 3-gallate, a natural compound mimicking lncRNA Gm31629.…”
Section: Ibd Treatments: Based On Experimentsmentioning
confidence: 99%
“…Targeting specific lncRNAs and miRNAs for silencing or overexpression provides therapeutic benefits, such as the inhibition of miR-222-3p for relieving DSS-induced damage of the colon. 139 Another approach is to utilize lncRNAs and miRNAs as potential therapeutic agents to target the relevant pathogenic factors. A noteworthy example of this is theaflavin 3-gallate, a natural compound mimicking lncRNA Gm31629.…”
Section: Ibd Treatments: Based On Experimentsmentioning
confidence: 99%
“…MDSC infiltration is often seen at sites of inflammation in patients with chronic inflammatory diseases and tumor, relevant studies have shown that certain pro-inflammatory mediators present in the microenvironment, like IL-6, contribute to the promotion of MDSC accumulation in the pathological state of chronic inflammation and malignancy (Laws et al 2023 ). Prostaglandin E2 (PGE2) is a significant lipid mediator that produced in the sustained inflammatory response, also further recruits MDSC, which in chronic inflammation further produce S100A8/A9 proteins, these calcium-binding proteins are mainly secreted by neutrophils and activated monocytes, and interestingly, these proteins in the inflammatory microenvironment in the inflammatory microenvironment further recruiting more MDSC causing further MDSC accumulation, the inflammatory microenvironment can also further increase the generation of reactive oxygen species (ROS) and pro-angiogenic factors like vascular endothelial growth factor (VEGF), which can contribute to MDSC accumulation and immunosuppressive activity, in addition, the tumor microenvironment and persistent inflammatory stimuli can also lead to an additional boost in the production of tumor necrosis factor alpha (TNF-α) by tumor cells, which also further recruits MDSC and enhances MDSC-associated immunosuppressive activity (Wang et al 2023a , b , c , d , e ). Multiple research studies have consistently shown that reducing MDSCs can effectively slow down tumor progression and lead to anti-tumor effects, and all these evidences suggest that MDSCs play unique and crucial roles in the progression of inflammatory bowel disease to CAC development (Krishnamoorthy et al 2021 ; Liao et al 2019 ; Wang et al 2023e ).…”
Section: Mdsc and Colitis-associated Colorectal Cancermentioning
confidence: 99%
“…Additionally, STAT3 was found to increase the expression of S100A8/9 proteins, which promotes the clustering of MDSCs in the tumor microenvironment (TME). This clustering ultimately leads to the activation and multiplication of MDSCs (Wang et al 2023a , b , c , d , e ). Using single-cell cytokine profiling for immunoassay, G. Qin et al found that MDSCs were significantly expressed in both clinical samples and mouse models of tumors, Additionally, they observed that specific factors like GM-CSF, G-CSF, IL-6, VEGF, etc., amplified the quantity of MDSCs in the tumor microenvironment and impeded their subsequent differentiation, and these factors further activated the JAK/STAT signaling pathway to stimulate myeloid cell production and promote MDSC expansion (Qin et al 2023 ).…”
Section: Mdsc and Colitis-associated Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…SLC6A14 promotes ferroptosis of epithelial cells through the C/EBPβ‐PAK6 axis of UC 5 . Inhibition of miR‐222‐3p reduces oxidative damage to activate Nrf2/HO‐1 signaling by targeting BRG1, thereby improving UC and colorectal cancer 6 . ACSF2 can mediate ferroptosis to participate in the progression of UC 7 .…”
Section: Introductionmentioning
confidence: 99%